2017
DOI: 10.1039/c6sm01846g
|View full text |Cite
|
Sign up to set email alerts
|

Optical control of surface forces and instabilities in foam films using photosurfactants

Abstract: Molecular interactions in thin liquid films, such as the disjoining pressure, are involved in interfacial phenomena such as emulsion and foam stabilization. In this article we show that through light stimulation we can control remotely the disjoining pressure in a thin liquid film stabilized by a photosurfactant. We stabilize a horizontal thin liquid film using a cationic photosurfactant, AzoTAB, bearing an azobenzene moiety on the hydrophobic tail which can switch from a trans to a cis conformation upon light… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 35 publications
3
23
0
Order By: Relevance
“…As a representative example, a thin film pressure balance (TFPB) represents a convenient system where nanoscale properties can be precisely controlled and investigated in a relatively easy manner as shown in numerous studies. [47][48][49][50][51][52] In this work, we have focused on the gas transport across soap films by means of predictive multiscale numerical models. In particular, we used a combination of molecular and continuum models to characterise and study the transport of gases through soap film membranes.…”
Section: Discussionmentioning
confidence: 99%
“…As a representative example, a thin film pressure balance (TFPB) represents a convenient system where nanoscale properties can be precisely controlled and investigated in a relatively easy manner as shown in numerous studies. [47][48][49][50][51][52] In this work, we have focused on the gas transport across soap films by means of predictive multiscale numerical models. In particular, we used a combination of molecular and continuum models to characterise and study the transport of gases through soap film membranes.…”
Section: Discussionmentioning
confidence: 99%
“…The results obtained from experiments with macroscopic foams showed that the light‐induced flow can slow down the foam drainage at the early stage of UV light irradiation, while a rapid rupture of foams was subsequently observed. Next, the influence of illumination on disjoining pressures of thin liquid films in identical foam systems was investigated, suggesting that the UV‐light‐induced rupture of foams was due to a decrease of electrostatic repulsion in the thin foam film as well as the oscillation of the disjoining pressure isotherm [132] . This systematic study of an amphiphile‐based photoresponsive system at the air–water interface emphasizes the prospects for application in remote control (by light) of foam stability.…”
Section: Dynamic Functions Of Photoresponsive Molecular Amphiphiles In Gibbs Monolayersmentioning
confidence: 95%
“…The above methods are either energy intensive or require chemical additives or specific monomers. There is also a significant body of work describing photo‐switchable surfactants . Recently, Kondo and coworkers demonstrated that UV light can be used to trigger demulsification of oil droplets dispersed in water stabilized by diazene‐based surfactants .…”
Section: Methodsmentioning
confidence: 99%
“…There is also a significant body of work describing photoswitchable surfactants. [19][20][21][22][23][24] Recently, Kondo and coworkers demonstrated that UV light can be used to trigger demulsification of oil droplets dispersed in water stabilized by diazenebased surfactants. [25,26] Diazene-based surfactants are able to undergo trans-cis isomerization when irradiated by UV-light (Scheme 1A) -the trans form is a more effective surfactant than the cis form.…”
mentioning
confidence: 99%